2011
DOI: 10.1016/j.exger.2011.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Aging effects on the control of grip force magnitude: An fMRI study

Abstract: Functional neuroimaging techniques have allowed for investigations into the mechanisms of agerelated deterioration in motor control. This study used functional Magnetic Resonance Imaging (fMRI) to investigate age related differences in the control of grip force magnitude. Using an event-related design, fMRI scans were completed on 13 older adults, and 13 gender matched younger adults, while using their dominant hand to squeeze a rubber bulb for 4s at 10%, 40% or 70% of their maximum voluntary contraction. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
57
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 46 publications
(92 reference statements)
8
57
1
Order By: Relevance
“…In particular, increased activation and involvement of a widespread motor network in elderly subjects have been suggested by means of electroencephalography (EEG; Babiloni et al 2006;Derambure et al 1993;Sailer et al 2000) and functional magnetic resonance imaging (fMRI) studies (Heuninckx et al 2005;Noble et al 2011;Ward and Frackowiak 2003). Additionally, slowing of brain dynamics has been evidenced with increasing age (Krampe 2002;Seidler et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, increased activation and involvement of a widespread motor network in elderly subjects have been suggested by means of electroencephalography (EEG; Babiloni et al 2006;Derambure et al 1993;Sailer et al 2000) and functional magnetic resonance imaging (fMRI) studies (Heuninckx et al 2005;Noble et al 2011;Ward and Frackowiak 2003). Additionally, slowing of brain dynamics has been evidenced with increasing age (Krampe 2002;Seidler et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This theory suggests that with aging there is a compensatory shift in neural recruitment to accommodate cognitive challenge (Park & Reuter-Lornez, 2009;Cooper et al, 2013). While the present study focused solely on the activation of the PFC, other brain regions are involved in fatigue development, particularly in older adults (Liu et al, 2003;Clark & Taylor, 2011;Noble et al, 2011). Previous research has demonstrated a shift in activation centers in the brain to maintain neuromuscular performance during a fatiguing protocol (Liu et al, 2007).…”
Section: Discussionmentioning
confidence: 89%
“…Second, the present study monitored the PFC regions due to equipment constraints. Existing neuroimaging investigations of fatigue development suggest a shift in activation centers in the brain to compensate for fatigue-related loss in neural efficiency, particularly with the normal aging process (Liu et al, 2007;Clark & Taylor, 2011;Noble et al, 2011), future research should examine activation of motor function-related brain regions to understand age-related changes in functional brain activation patterns when individuals are physically and cognitively fatigued. Third, while all participants reported that the 60-minute working memory tasks were cognitively fatiguing, it is possible that longer exposure to such stressors may result in greater negative effects of cognitive fatigue on neuromuscular function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations